Effects of Writing Position on Handwriting in Forensic Analysis - Kumari, Ritu; Sharma, Bhoopesh Kumar; Dhillon, Deepika; Puja, Kumari (Journal of Neonatal Surgery, 2025)
Handwriting is a distinct characteristic influenced by individual motor skills, cognitive aptitude, and surrounding circumstances. Forensic handwriting analysis is critical in determining the authenticity of documents, especially in legal conflicts involving contested wills or contracts. The study collected 180 handwriting samples from 60 individuals, each writing in three different positions on plain A4 paper with a Reynolds Ballpoint pen (0.7mm). The primary handwriting qualities examined were writing slant, alignment, letter size, fluency, letter spacing, and pen pressure. Statistical analysis was used to see if writing position had any effect on these characteristics. The findings revealed no significant variation in slant or alignment across different writing positions. However, there were significant changes in letter size, fluency, spacing between letters, and pen pressure. The findings indicate that, whereas body position has little effect on slant or alignment, it does have a significant impact on letter size, fluency, spacing, and pen pressure. Furthermore, variations in writing position might have an impact on various handwriting traits that should be taken consideration during forensic document inspection. This study helps understand handwriting diversity and highlights the relevance of body posture in forensic investigation.